Local Culinary Entrepreneurship As The Development Of Regional Gastronomy And Urban Tourism - Arfah Sahabudin (Khazanah Intelektual, 2022)
Tourism development efforts are currently being pursued through the concept of sustainable tourism with a community-based tourism approach, providing great opportunities for the community to participate in tourism development; produce tourism product development from businesses managed by the community. However, a way is still needed so that all these developments can continue to increase the number of tourist visits. The emergence of tourism as an academic part of tourism studies and education, encourages tourism potential to continue to be developed. Such an attraction makes Sate Bandeng a gastronomic tour. Which is one of the right ways to raise the potential of local culinary. This article aims to show the progress of tourism since before the concept of sustainable tourism was applied to the present. The research method used is a description with a qualitative approach. This study is based on a review of secondary sources through literature research and personal communication with several scholars in tourism and tourism business services. There are not many articles that discuss local culinary entrepreneurship as a development of regional gastronomy and part of an urban tourism attraction, while the development of sustainable tourism has allowed tourism to stand alone, and it seems that tourism with all its derivatives has gained independence as a field of academic study and as a Study Program in Higher Education in Indonesia. Indonesia.